2012
DOI: 10.1158/1078-0432.ccr-11-1625
|View full text |Cite
|
Sign up to set email alerts
|

VTX-2337 Is a Novel TLR8 Agonist That Activates NK Cells and Augments ADCC

Abstract: Purpose: We aim to characterize VTX-2337, a novel Toll-like receptor (TLR) 8 agonist in clinical development, and investigate its potential to improve monoclonal antibody-based immunotherapy that includes the activation of natural killer (NK) cells.Experimental Design: HEK-TLR transfectants were used to compare the selectivity and potency of VTX-2337, imiquimod, CpG ODN2006, and CL075. The ability of VTX-2337 to induce cytokine and chemokine production from human peripheral blood mononuclear cells (PBMC) and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
153
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(162 citation statements)
references
References 41 publications
9
153
0
Order By: Relevance
“…We have extensively characterized the in vitro response of human peripheral blood mononuclear cells, monocytes, mDC, and NK cells to VTX-2337 (6). It should be noted that many of the prominent cytokines induced in vitro via TLR8 activation (notably, IL12, IL1, IFNg) are not detected in the plasma of subjects dosed with VTX-2337.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have extensively characterized the in vitro response of human peripheral blood mononuclear cells, monocytes, mDC, and NK cells to VTX-2337 (6). It should be noted that many of the prominent cytokines induced in vitro via TLR8 activation (notably, IL12, IL1, IFNg) are not detected in the plasma of subjects dosed with VTX-2337.…”
Section: Discussionmentioning
confidence: 99%
“…Recent X-ray crystallographic data have confirmed that this LRR is associated with ligand binding (10). In all other species, TLR8 is a potent activator of innate immunity, and in humans TLR8 is expressed in the endosomal compartment of monocytes and mDC (6,11). This is in clear distinction to the expression of human TLR7 and TLR9 in the endosome of plasmacytoid dendritic cells-a population of DC with a very different phenotype and biology compared with mDC (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…And more important is that unlike other TLR7/8 agonists, these ssRNAs can mediate the activation of NK cells directly, represented as up-regulation of cytotoxicity against HNSCC cell lines BHY, PCI-1 and PCI-13, induction production of IFN-, granzyme B and perforin by NK cells [53]. VTX-2337, a novel small-molecular TLR8 agonist, is recently found to be able to activate NK cells directly and augment ADCC by rituximab in PBMCs [54]. Stimulation with imiquimod, also known as a TLR7 ligand, enhances the cytotoxic activity of expanded NK and  T cells from cancer patients in vitro [55].…”
Section: Tlr Signaling On Nk Cell Activationmentioning
confidence: 99%